Technical and surgical aspects of the sphenopalatine ganglion (SPG) microstimulator insertion procedure. Issue 2 (February 2016) - Assaf, A.T.; Hillerup, S.; Rostgaard, J.; Puche, M.; Blessmann, M.; Kohlmeier, C.; Pohlenz, P.; Klatt, J.C.; Heiland, M.; Caparso, A.; Papay, F.
Abstract: Cluster headache (CH) is a debilitating, severe form of headache. A novel non-systemic therapy has been developed that produces therapeutic electrical stimulation to the sphenopalatine ganglion (SPG). A transoral surgical technique for inserting the Pulsante SPG Microstimulator into the pterygopalatine fossa (PPF) is presented herein. Technical aspects include detailed descriptions of the preoperative planning using computed tomography or cone beam computed tomography scans for presurgical digital microstimulator insertion into the patient-specific anatomy and intraoperative verification of microstimulator placement. Surgical aspects include techniques to insert the microstimulator into the proper midface location atraumatically. During the Pathway CH-1 and Pathway R-1 studies, 99 CH patients received an SPG microstimulator. Ninety-six had a microstimulator placed within the PPF during their initial procedure. Perioperative surgical sequelae included sensory disturbances, pain, and swelling. Follow-up procedures included placement of a second microstimulator on the opposite side ( n  = 2), adjustment of the microstimulator lead location ( n  = 13), re-placement after initial unsuccessful placement ( n  = 1), and removal ( n  = 5). This SPG microstimulator insertion procedure has sequelae comparable to other oral cavity procedures including tooth extractions, sinus surgery, and dental implant placement. Twenty-five of 29 subjects (86%) completing a self-assessment questionnaire indicated that the surgical effects were tolerable and 90% would make the same decision again.